SghC1q, a novel C1q family member from half-smooth tongue sole (Cynoglossus semilaevis): Identification, expression and analysis of antibacterial and antiviral activities. Issue 1 (January 2015) - Zeng, Yan; Xiang, Jinsong; Lu, Yang; Chen, Yadong; Wang, Tianzi; Gong, Guangye; Wang, Lei; Li, Xihong; Chen, Songlin; Sha, Zhenxia
Highlights The full-length cDNA of CssghC1q is 905 bp, and the genomic DNA sequence is 1562 bp. The deduced protein of CssghC1q contains a C1q domain. CssghC1q shows particular expression patterns according to the tissue after pathogen infection. Recombinant CssghC1q protein exhibited antibacterial and antiviral activities.